Application Of Path-Goal Leadership Theory And Learning Theory In A Learning Organization - Farhan, Bayan Yousef (Journal of Applied Business Research, 2017)
This paper used learning theory and path-goal theory to propose a learning leadership model. The practical side of these two theories is suitable for this proposed model, its agenda, and its tools for improving organizational learning. The model is based on the assumption that leaders need to develop their competences and the competences of subordinates by creating a continuous learning process through sharing, exchanging, and improving knowledge and experiences. The model states that learning leaders act as facilitators of the organizational learning process and adopt the right attitude to motivate subordinates for learning by removing obstacles and creating a learning culture.